C++ All-In-One : for dummies - Meuller, John Paul, ....- (New Jersey : John Wiley & Sons, 2021)
Your comprehensive and updated guide to one of the world’s most popular programming languages is here! Whether you’re a novice or expert, you’ll find what you need to get going with the latest features of C++20. The workhorse of programming languages, C++ gives you the utmost control of data usage and interface and resource allocation. If your job involves data, proficiency in C++ means you’re indispensable! This edition gives you 8 books in 1 for total C++ mastery. Inside, internationally renowned expert John Paul Mueller takes you from the fundamentals of working with objects and classes to writing applications that use paradigms not normally associated with C++, such as those used for functional programming strategies. The book also includes online resources such as source code. You discover how to use a C++ GNU compiler to build applications and even how to use your mobile device for coding.
Keywords: Programmeren; Python